1988
DOI: 10.1083/jcb.106.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of fibroblast functions by interleukin 1: increased steady-state accumulation of type I procollagen messenger RNAs and stimulation of other functions but not chemotaxis by human recombinant interleukin 1 alpha and beta

Abstract: Abstract. Interleukin-I (IL-1) is synthesized by and released from macrophages in response to a variety of stimuli and appears to play an essential role in virtually all inflammatory conditions. In tissues of mesenchymal origin (e.g., cartilage, muscle, bone, and soft connective tissue) ILl induces changes characteristic of both destructive as well as reparative phenomena. Previous studies with natural IL-1 of varying degrees of purity have suggested that it is capable of modulating a number of biological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(114 citation statements)
references
References 40 publications
1
108
0
2
Order By: Relevance
“…It has already been demonstrated that unspecified lymphocyte products (Johnson & Ziff, 1976;Postlethwaite et al, 1984), unspecified T-cell products (Wahl & Gately, 1983), interleukin-l, which is produced by many cells including T-cells (Goldring & Krane, 1987;Postlethwaite et al, 1988), and transforming growth factor beta, produced by T-cells and macrophages (Roberts et al, 1986;Raghow et al, 1987), influence collagen production by cultured fibroblasts. The depletion of T-cells inhibited the formation of bacterial cell wall-induced hepatic granulomas in vivo (Wahl et al, 1986), and reduced the ability of immune spleen cells to form granulomas around Schistosoma eggs in vitro (Bentley et al, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…It has already been demonstrated that unspecified lymphocyte products (Johnson & Ziff, 1976;Postlethwaite et al, 1984), unspecified T-cell products (Wahl & Gately, 1983), interleukin-l, which is produced by many cells including T-cells (Goldring & Krane, 1987;Postlethwaite et al, 1988), and transforming growth factor beta, produced by T-cells and macrophages (Roberts et al, 1986;Raghow et al, 1987), influence collagen production by cultured fibroblasts. The depletion of T-cells inhibited the formation of bacterial cell wall-induced hepatic granulomas in vivo (Wahl et al, 1986), and reduced the ability of immune spleen cells to form granulomas around Schistosoma eggs in vitro (Bentley et al, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies demonstrate that IL-1β can stimulate collagen expression in a dose-dependent manner [48]. Because IL-1β can induce its own gene expression, chronic activation of the inflammasome resulting in the continual cleavage of IL-1β in a positive feedback mechanism could conceivably maintain a high level of active TGF-β1 protein resulting in fibrosis [49].…”
Section: Relationship Between P2x 7 R and Fibrosismentioning
confidence: 99%
“…35 IL-1 and TNF-␣ have been shown to upregulate the expression of matrix metalloproteinases (MMPs) in fibroblasts, especially MMP-1 and MMP-3. 36,37 In general, MMPs favor the degradation of extracellular matrix, with its collagen, laminin and basal membrane components, thus slowing deposition of the necessary cellular matrix, wound closure and re-epithelialization.…”
Section: Figure 3 (A) Serum Haptoglobin Levels Serum Haptoglobin Levmentioning
confidence: 99%
“…The IGF-1 modulation of the cytokine release after burn trauma appears to contribute to the observed improvement in wound healing. 34,35 The IGF-1 effects on inflammatory and anti-inflammatory cytokine expression may also influence extracellular matrix deposition and thus improve eventual wound breaking strength. 10,31 Although, there were significant differences in the local cytokine mRNA levels in burned animals after treatment with IGF-1 cDNA gene transfer compared with untreated burn animals, systemic serum cytokine levels for TNF-␣, IL-1␤, and IL-6 proteins did not show any significant changes in either treated or untreated burned rats.…”
Section: Figure 3 (A) Serum Haptoglobin Levels Serum Haptoglobin Levmentioning
confidence: 99%